Systematic Literature Review: The Role Of Internal Audit On Accounting Fraud In Indonesia 2020/2025 Period - Al Dzahabi Rachman; Enggar Diah Puspa Arum; Wira Lestari (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyze the role of internal audit in preventing accounting fraud in Indonesian organizations during the period 2020–2025. Using the Systematic Literature Review (SLR) method, this research examines 10 national journal articles indexed by SINTA that discuss internal audit, internal control, and fraud prevention. Thematic analysis was employed to identify repeated patterns across studies. The findings show that internal audit plays a significant role in detecting and preventing fraud through monitoring activities, strengthening internal control systems, and supporting good corporate governance. Auditor competence and independence are identified as essential determinants of audit effectiveness. The study also highlights the growing importance of technology-based audits (digital audit) in enhancing fraud detection. This review contributes to providing a comprehensive understanding of recent developments in internal audit practices in Indonesia.